2012
DOI: 10.1109/tdei.2012.6396954
|View full text |Cite
|
Sign up to set email alerts
|

The depletion of dibenzyl disulfide from a mineral transformer insulating oil

Abstract: This study examines the kinetics of the net depletion of dibenzyl disulfide (DBDS) from its solution in mineral insulating oil due to copper corrosion at elevated temperatures in power transformers. The concentration of DBDS is determined using liquid-liquid extraction followed by GC detection. Measurements, at 24 h intervals, up to 168 h, show that the depletion of DBDS from its solutions in mineral insulating oil at 150 C and initial concentrations of 3.00, 6.00, 9.00, 12.00 and 15.00 mg L −1 is very slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Under operation conditions, DBDS is known to further copper corrosion in electric equipment, by forming copper (I) sulfide Cu2S as the main product, with the subsequent production of other sulfur compounds such as benzyl sulfide and dibenzyl sulphide. In spite of successive studies about the chemical phenomenon, the mechanism remains unclear [39][40][41][42] . Since DBDS is related to the commonly used thiol molecules, in the well-known thiol self-assembled monolayers (SAM) on metal surfaces, 9,[43][44][45] , the analysis of the metal-sulfur bond is important to complete the already known information on the chemical properties of this type of systems.…”
Section: Introductionmentioning
confidence: 99%
“…Under operation conditions, DBDS is known to further copper corrosion in electric equipment, by forming copper (I) sulfide Cu2S as the main product, with the subsequent production of other sulfur compounds such as benzyl sulfide and dibenzyl sulphide. In spite of successive studies about the chemical phenomenon, the mechanism remains unclear [39][40][41][42] . Since DBDS is related to the commonly used thiol molecules, in the well-known thiol self-assembled monolayers (SAM) on metal surfaces, 9,[43][44][45] , the analysis of the metal-sulfur bond is important to complete the already known information on the chemical properties of this type of systems.…”
Section: Introductionmentioning
confidence: 99%
“…They verified the aforementioned research results and found that DBDS can react completely in different oxygen concentration, as well as the reaction process does not need oxygen to participate. Regarding the concentration of sulphur corrosion, experiments also have shown that even the DBDS concentration as low as 1 mg/L will cause sulphur corrosion, and the content of most dissolved gases in the oil and the acid value in the oil would increase [8]. Scholars have also carried out a lot of research work on the influencing factors of corrosive sulfides [9][10][11], and find that the external conditions such as electric field [9], oxygen [10], temperature [11] and other factors also have an important influence on the formation of sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, the sulfide deposition phenomenon was discovered successively in transformer fault inspections of 220 kV and above voltage classes in areas within China Southern Power Grid, East China, and North China [5,6]. Studies and reports on corrosive sulfur faults were also conducted in other countries such as Japan, Europe and other countries [7,8]. The insulation fault caused by sulfur corrosion has become a major threat to the safe operation of oil-immersed power transformers.…”
Section: Introductionmentioning
confidence: 99%